Mappaenre Doi dalam Perspektif Fikih Munakahat (Studi Kasus Adat Pernikahan Suku Bugis di Lampu Satu Samkai Merauke): Mappaenre Doi in Fiqh of Munākaḥāt Perspective (Case Study of Bugis Tribe Wedding Traditions in Lampu Satu Samkai Merauke) - Nurdiah, Nurdiah; Yulia Rahman, Hendra; Al Abza, M. Thohar (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Mappaenre Doi is a tradition in the Bugis tribe that is carried out before the wedding ceremony. Perspectives on the Mappanri Doi tradition in the Bugis community and among the scholars have differences. This study aims to analyze the process of Mappaenre Doi of Bugis custom in Merauke and to analyze the implications of Mappaenre Doi in the perspective of fikih munakahat. This type of research is qualitative. The data collection technique used is the exploratory method through observation, interviews, and documentation conducted in Lampu Satu Samkai Village, Merauke Regency, for three months starting from March 2023 to June 2023. The data obtained was tested for validity using credibility and triangulation tests, and then analyzed descriptively. The results showed that: 1) Mappaenre Doi process, namely: a) the male family negotiates with the female party to discuss the nominal amount of Mappaenre Doi money until reaching an agreement; b) determine when the male family will meet to submit the agreed Mappaenre Doi; c) the male party visits the female party's house to submit Mappaenre Doi; and d) determine the time of marriage when Mappaenre Doi has been submitted. 2) The implication of Mappanrae Doi in the perspective of fikih munakahat is the process of negotiating the provision of dowry to the prospective wife, and it is recommended to the woman not to ask for excessive dowry, as long as it does not violate sharia principles. The study of this research shows that the Mappaenre Doi process in the Bugis traditional marriage tradition in Merauke Regency is determined through negotiations between the families of the male and female parties, and the Mappaenre Doi tradition is valid according to Islamic law.